2022
DOI: 10.1186/s12880-022-00940-0
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular invasion risk scores affect the estimation of early recurrence after resection in patients with hepatocellular carcinoma: a retrospective study

Abstract: Background Microvascular invasion (MVI) is a histological factor that is closely related to the early recurrence of hepatocellular carcinoma (HCC) after resection. To investigate whether a noninvasive risk score system based on MVI status can be established to estimate early recurrence of HCC after resection. Methods Between January 2018 to March 2021, a total of 108 patients with surgically treated single HCC was retrospectively included in our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…MVI was found to be one of the most critical factors in predicting recurrence and survival outcomes. Approximately more than 60% of all HCC recurrences are early recurrences which are closely related to presence of MVI[ 17 , 18 ]. The present study confirmed MVI was an important predictive factor for early recurrence of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…MVI was found to be one of the most critical factors in predicting recurrence and survival outcomes. Approximately more than 60% of all HCC recurrences are early recurrences which are closely related to presence of MVI[ 17 , 18 ]. The present study confirmed MVI was an important predictive factor for early recurrence of HCC.…”
Section: Discussionmentioning
confidence: 99%